2021
DOI: 10.22175/mmb.11598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pork Quality Types, Packaging, and Degree of Doneness on Trained Sensory and Instrumental Tenderness, Color, and Consumer Perception

Abstract: The objective of this study was to evaluate the palatability and retail display differences of 3 types of pork loins. Enhanced (n = 10), nonenhanced (n = 10), and high-quality (n = 10) pork loins were selected from a commercial food distribution company. Loins were cut into 2.54-cm-thick chops and randomly assigned to retail display, sensory, or Warner-Bratzler shear force analyses. For retail display, chops were randomly assigned to 1 of 3 packaging treatments: polyvinyl chloride overwrap, carbon monoxide-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…One of the most significant benefits of MAP is its capacity to suppress the growth of spoilage bacteria and so improve the shelf life of food goods (Hosseini et al, 2021).By changing the composition of the gas, MAP provides an environment unfriendly to the growth of bacteria, yeast, and molds, lowering the risk of microbiological deterioration (Goulas et al, 2005).This is especially significant for high-moisture products like bakery items, where microbial deterioration is a major issue (R occa-Smith et al, 2016).MAP can also aid in the preservation of the color and look of meat products by improving the stability and consistency of meat color and helping protect the sensory and nutritional quality of food products in addition to microbial control. MAP can decrease the oxidation of lipids and other sensitive components in the package by lowering the oxygen content (Cassens et al, 2021). MAP can also aid in the prevention of off-flavors and odors that can develop during storage (Hosseini et al, 2021).…”
Section: C) Modified Atmosphere Packaging (Map)mentioning
confidence: 99%
“…One of the most significant benefits of MAP is its capacity to suppress the growth of spoilage bacteria and so improve the shelf life of food goods (Hosseini et al, 2021).By changing the composition of the gas, MAP provides an environment unfriendly to the growth of bacteria, yeast, and molds, lowering the risk of microbiological deterioration (Goulas et al, 2005).This is especially significant for high-moisture products like bakery items, where microbial deterioration is a major issue (R occa-Smith et al, 2016).MAP can also aid in the preservation of the color and look of meat products by improving the stability and consistency of meat color and helping protect the sensory and nutritional quality of food products in addition to microbial control. MAP can decrease the oxidation of lipids and other sensitive components in the package by lowering the oxygen content (Cassens et al, 2021). MAP can also aid in the prevention of off-flavors and odors that can develop during storage (Hosseini et al, 2021).…”
Section: C) Modified Atmosphere Packaging (Map)mentioning
confidence: 99%
“…Previous research has utilized both instrumental and visual color to characterize color changes, and some studies determined the relationship between instrumental color and visual panel/web-based color evaluation (Eagerman et al, 1977(Eagerman et al, , 1978Harrison et al, 1980;Holman et al, 2016;Wills et al, 2017;Cassens et al, 2021;Yoder et al, 2021). Although instrument settings such as illuminant and aperture size can influence color measurements, Tapp et al (2011) reported that a significant amount of published research does not report several instrumental parameters (such as illuminant or aperture size) as suggested by the AMSA Color Guidelines (2012).…”
Section: Introductionmentioning
confidence: 99%
“…CO-MAP is used in the beef industry during the transportation of meat in mother bags to create anaerobic conditions and maintains acceptable consumer color and shelf life. In addition, when used along with other gases such as CO, nitrogen (N 2 ), and CO 2 , meat has better flavor acceptability, no bone darkening, no premature browning during cooking, and improved tenderness (John et al, 2005;Cornforth and Hunt, 2008;Suman et al, 2011;Denzer et al, 2020;Cassens et al, 2021). Fraqueza and Barreto (2011) reported a shelf life of 25 d for turkey fillets stored at 0°C under MAP consisting of 0.5% CO, 80% CO 2 , and 19.5% N 2 relative to 5 d of shelf life for aerobically packaged meat.…”
Section: Introductionmentioning
confidence: 99%